Improving the local formability of a AA7075 aluminum alloy by laser-induced modification of the alloying concept - Zieroth, Henrik; Stephan, Marcel; Schmidt, Michael; Merklein, Marion (MATEC Web of Conferences, 2025)
With expanding applications in aerospace, automotive, and advanced manufacturing, the need for adaptable materials with tailored mechanical properties is pressing. This study presents a novel approach for selective element adaptation, applied to AA7075 - a high-strength aluminum alloy valued for its exceptional strength but limited by low ductility. Through controlled vaporization of zinc (Zn) and magnesium (Mg), this method enables targeted adjustments in local properties to enhance formability. To evaluate process stability, a comparison was conducted between standard linear vaporization and an advanced double-beam technique, leveraging an optical system that splits and aligns the collimated laser beam for enhanced control. Formability is assessed via 3-point bending tests at varying angles, contrasting vaporized AA7075 with both an exclusively vaporized variant and a silicon-alloyed version approximating the ductility profile of 6xxx alloys. Findings indicate that element-adapted blanks, entitled as Tailored Alloyed Blanks (TAB), achieve significant improvements in localized formability and process stability, establishing a promising technique for the development of adaptable, high-strength materials suited to complex component designs and diverse industrial application
Keywords: Tailor Alloyed Blanks (TAB); laser beam welding; element evaporation; aluminum alloys